KEPEMIMPINAN DALAM PERSPEKTIF TEOLOGI ISLAM - yeni arum adiningsih (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
leadership is a way for someone to lead, there are several things why leaders are needed. First, humans naturally need to be regulated. Secondly in certain conditions a leader needs to appear on behalf of his group. Third, as the holder of responsibility if a problem or risk occurs. Fourth, as the holder and place of power. A leader not only regulates the people who are stagnant and easy to manage but also can control himself to remain productive like humans in general who always obey the ego and win themselves. Islam also discusses leadership, as revealed in the Koran that God created human beings on this earth, one of which is a leader who is able to manage and protect nature well, and does not cause damage. This article is aimed at discovering how leadership is in the perspective of Islamic theology. This article is a research library (library research) with data collection methods sourced from books and journals related to research, by reading, understanding, and analyzing existing research sources. With the results of research that in Islam, leadership is divided into 3 terms, namely the caliph, imamat and imarah. Basically, a leader in Islamic theology is not only a government leader in the state, but also a religious leader, with a ma'sum.